Analysis of Decision Making in Vendor Selection on the TKDN Value Limit Based on the Decree of the Minister of PUPR NO.602/KPTS/M/2023 - Arfyan, Aslam Rizki; Kurniyaningrum, Endah; Pontan, Darmawan; Kusumawati, Lili (Green Publisher Indonesia, 2025)
In the procurement process for goods and services, the use of domestic products is emphasized in Government Regulation No. 29 of 2018 regarding Industrial Empowerment, which mandates the use of Domestic Products (PDN) with a minimum Domestic Component Level (TKDN) of 40%. This regulation, outlined in Article 57, focuses on the inclusion of domestic components in various products and services, including construction works, which must adhere to TKDN provisions. The Ministry of Public Works and Public Housing (PUPR) has taken significant steps to support the use of domestic products by establishing the 2022-2024 Domestic Product Improvement Team (P3DN) in March 2022, followed by the issuance of Presidential Instruction No. 2 of 2022. This aims to accelerate the use of domestic products and promote small businesses through the National Movement Proud of Made in Indonesia. The TKDN is calculated based on the proportion of locally sourced materials and equipment in a product or service, and construction sectors like highways, dams, and irrigation works fall under the purview of various directorates at the Ministry of PUPR. This study investigates how these policies influence the procurement decisions in infrastructure projects and the impact of TKDN on vendor selection processes, particularly in large-scale construction projects such as road building and bridge construction. The findings are expected to contribute to a better understanding of TKDN implementation in the construction industry, offering insights into the challenges and opportunities of integrating domestic products into public procurement.